Acceptance of illness and social, individual factors as the predictors of quality of life in hypertensive patients - Samira Khatar; Leila Mirhadyan; Homa Mosaffa Khomami; Ehsan Kazemnejad Leili (Tehran University of Medical Sciences, 2023)
Background & Aim: Many factors affect the hypertensive patients' quality of life. Identifying the factors related to the quality of life can help to promote the quality of life in hypertensive patients. This study aimed to determine the predictive role of illness acceptance and social, individual factors in the hypertensive patients' quality of life. Methods & Materials: This correlational, cross-section study was conducted in 2020-2021 on 245 hypertensive patients referred to a hypertension clinic in Lahijan selected by the convenience sampling method. Data were collected by a questionnaire, including demographic information, Acceptance of Illness Scale and the WHO's Quality of Life-Brief questionnaire. Data were analyzed by multiple linear regression at a 95% confidence level using the SPSS software version 23. Results: The mean score for the quality of life was 65.32±12.18 (0-100) and for the acceptance of illness was 31.83±4.98 (8-40). Age, sex, employment status, marital status, monthly income, family arrangement and the acceptance of illness were identified as the predictors of quality of life in hypertensive patients (P<0.001). According to the coefficient of determination (R2=0.401), the variables of the final regression model explained about 40% of the quality-of-life changes among hypertensive patients. Conclusion: Given that the acceptance of illness and some social, individual factors can affect the hypertensive patients' quality of life, focus on the strategies to promote the acceptance of illness and paying attention to social, individual factors can help improve the quality of life among hypertensive patients.